2007
DOI: 10.1371/journal.pone.0001189
|View full text |Cite
|
Sign up to set email alerts
|

Mining Predicted Essential Genes of Brugia malayi for Nematode Drug Targets

Abstract: We report results from the first genome-wide application of a rational drug target selection methodology to a metazoan pathogen genome, the completed draft sequence of Brugia malayi, a parasitic nematode responsible for human lymphatic filariasis. More than 1.5 billion people worldwide are at risk of contracting lymphatic filariasis and onchocerciasis, a related filarial disease. Drug treatments for filariasis have not changed significantly in over 20 years, and with the risk of resistance rising, there is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 75 publications
(88 reference statements)
1
81
0
1
Order By: Relevance
“…This suggests that orthologs of PFN-2 could serve as a novel target for disrupting intestinal membrane integrity in parasitic nematodes while not affecting the mammalian host. Likewise, GS_11702 is orthologous to the C. elegans glycolytic and gluconeogenic protein "cofactor-independent phosphoglycerate mutase" (iPGM; F57B10.3a), which has been previously identified as being conserved across nematodes but distinct from mammalian PGM (95,96). Although iPGM was previously considered an excellent potential drug target for the control of parasitic nematodes, studies have recently shown that it has limited druggability because of difficulty in accessing the active site (97).…”
Section: Functional Enrichment Analyses Reveal Known and Novel Functimentioning
confidence: 99%
“…This suggests that orthologs of PFN-2 could serve as a novel target for disrupting intestinal membrane integrity in parasitic nematodes while not affecting the mammalian host. Likewise, GS_11702 is orthologous to the C. elegans glycolytic and gluconeogenic protein "cofactor-independent phosphoglycerate mutase" (iPGM; F57B10.3a), which has been previously identified as being conserved across nematodes but distinct from mammalian PGM (95,96). Although iPGM was previously considered an excellent potential drug target for the control of parasitic nematodes, studies have recently shown that it has limited druggability because of difficulty in accessing the active site (97).…”
Section: Functional Enrichment Analyses Reveal Known and Novel Functimentioning
confidence: 99%
“…[1][2][3][4][5] Because a,a 0 -trehalose synthesis is restricted to plants and in particular to lower organisms, including parasitic nematodes, opportunistic fungi and pathogenic bacteria, T6PP has been identified as an attractive platform for the development of small molecule inhibitors to serve as antihelminthics, antifungals and antibacterials. 2,6,7 To this end, large quantities of homogenous T6P are required to support high-throughput inhibitor screening, evaluation and SAR analyses. However, commercial T6P is costly, and its contamination with inorganic phosphate interferes with the T6PP activity assay.…”
Section: Introductionmentioning
confidence: 99%
“…Since RNAi machinery is well characterized in C. elegans, this experimental system can provide a potent tool for unveiling gene functions in other nematodes via comparative genomics [101]. The feasibility of this approach has been recently demonstrated in B. malayi [102]. Using sequence analyses and comparisons including gene functional studies with RNAi knockdowns in C. elegans, 589 B. malayi genes were identified as being critical to the survival of the filarial worm, representing potential targets for antifilarial drug discovery.…”
Section: Current Obstacles and Future Prospects Of Rnai In Helminthsmentioning
confidence: 99%